Trauma Analysis of the Main Characters in the Novel a Thousand Splendid Suns (2007) - Nurul Azkya; Nia Nafisah (Passage: Journal of English Language and Literature, 2024)
Nowadays, the issue regarding trauma and its impacts have been raised seriously in society. This issue is important to understand because trauma can have a negative influence on one's life. Trauma could be understood from various media and sources among us, such as literary works that represent trauma. This study aims to analyze trauma in the novel A Thousand Splendid Suns (2007) by Khaled Hosseini. This study unveils the traumatic events experienced by the main characters, the trauma responses illustrated by the main characters, and the sources of trauma. In analyzing the data from the novel, this study used a qualitative design and textual analysis method. The data collection process was carried out by close reading the novel, and then the data were highlighted and annotated. Subsequently, the data were identified and classified based on each character’s traumatic experiences, trauma responses, and its sources. By using Caruth’s concept of trauma (1995) and Vickroy’s trauma theory (2014), it was found that the main characters of the novel, Mariam and Laila, undergo similar traumatic experiences, and they illustrate different trauma responses. In addition, the sources of their traumas are the socio-cultural environment and political situation, which results in betrayal trauma and insidious trauma. It can be concluded that the socio-cultural environment can be a source of trauma if it fails to provide a safe and reliable environment, and it impacts one’s experience and understanding of trauma.